Effects of 24 weeks of collagen supplementation in active adults: Impact on body composition, neuromuscular and cardiorespiratory fitness - Aranda, Carlos Elvira; Sansó, Roser De Castellar; Rico, Loreto Lledó; Llorca, Concepción Suárez; Pérez Turpin, José Antonio (Biology of Sport, 2025)
The aim of this study was to analyze the effects of hydrolyzed collagen supplementation on body composition, neuromuscular fitness and cardiorespiratory fitness in active subjects undergoing a 24-week training program. A randomized, double-blind, placebo-controlled trial was conducted in 90 adults aged 45–65 with osteoarticular discomfort, including 45 men and 45 women. Participants received either 10g of hydrolyzed collagen enriched with minerals and vitamins (experimental group, EG), or a placebo (control group, CG), while following a twice-weekly training program. Physical performance was assessed through grip strength, squat jump (SJ), counter-movement jump (CMJ), and a cardiopulmonary exercise test. Biochemical and hematological analyses were also conducted. Significant improvements were observed in CMJ for the EG ( p = 0.032), with men showing greater gains than women ( p = 0.049). No significant differences were found in SJ between groups. After 24 weeks, 72.1% of the EG reported improved musculoskeletal discomfort, compared to only 10.3% of the CG. The study suggests that collagen supplementation may enhance muscle performance, likely by promoting connective tissue remodeling and increasing tendon elasticity. However, training alone improved overall physical condition in all participants.